Case Report: “Area of Focus” Atypical Trichinellosis and Fascioliasis Coinfection - Wang, Meng; Liu, Wei; Xiong, Ziman; Li, Zhen; Li, Jiansha; Xu, Xin; Zhang, Meng; Xing, Mingyou; Ning, Qin; Wu, Di; Qi, Junying (Frontiers in Medicine, 2022)
Parasitic co-infection is commonly observed in natural populations, yet rare in the laboratory. Multiparasitism can have negative effects on the host, ranging from the atypical manifestations to increased mortality, consequently, it may be misdiagnosed and treated with unsuitable anthelmintic medicines. Therefore, reliable diagnosis is critical for appropriate treatment of parasitic co-infection. Here, we report a case of a 31-year-old woman with persistent eosinophilia and hypoechoic liver lesion on ultrasound. The microscopic examination of stool samples did not find any pathogens. The patient had serum specific anti-Trichinella IgG antibody by enzyme linked immunosorbent assay (ELISA). After treatment with albendazole, contrast-enhanced magnetic resonance imaging (MRI) revealed more lesions in the liver. Subsequently, Fasciola hepatica was identified by metagenomic next-generation sequencing (mNGS) as well as polymerase chain reaction within the liver biopsy specimen. The eosinophil count returned normal, and the liver lesions were significantly absorbed after treatment with triclabendazole, first-line drug of Fasciola hepatica and larvae. This case highlights the diagnostic challenge posed by parasitic co-infection, which merits more in-depth evaluation to confirm the diagnosis.